Study guides

☆☆

Q: What are the common factors of 5x plus 10 and 6x2 plus 12x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3x(x2 + 2x - 4)

2x(3x+6) = 0 x = 0 or x = -2

6x2-2x+36 = 5x2+10x 6x2-5x2-2x-10x+36 = 0 x2-12x+36 = 0 (x-6)(x-6) = 0 x = 6 or x = 6 It has two equal roots.

6x2=12 2x-28=?

yes.it is.

Related questions

6x2 - 12x [take out what both terms have in common] 6x(x - 2) [if you multiply 6x by both terms in the parenthesis you will get your original answer]

2(3x^2 + 6x + 2)

3x(x2 + 2x - 4)

(3x+1)(2x+4) = 6x2+4+2x+12x = 6x2+14x+4

By additive factoring for ed. purposes.6X2 + 12X= 6X(X + 2)6X========common factor

2x(3x+6) = 0 x = 0 or x = -2

The expression may be : 6x2 + 17x + 12 This factors as, 6x2 + 17x + 12 = (3x + 4)(2x + 3) Or, the expression could be : 6x2 - 17x + 12 This factors as, 6x2 - 17x + 12 = (3x - 4)(2x - 3)

6x2 + 14x -12 = (3x - 2) (2x + 6). There they are.

6x2-2x+36 = 5x2+10x 6x2-5x2-2x-10x+36 = 0 x2-12x+36 = 0 (x-6)(x-6) = 0 x = 6 or x = 6 It has two equal roots.

(x + 2)(6x + 1)A:(x + 2)(6x + 1) is the factor of...6x2 + 13x + 2If that is what you are wanting. Which it looks like it may be.

9+6x2=21

First take out the common factor (4):4(6x2 + 2x + 1)6x2 + 2x + 1 cannot be factored, so 4(6x2 + 2x + 1) is as far as you can get with factoring.

People also asked